The Role of Digital Health in Supporting Privatization of Healthcare Services in health care sitting Saudi Arabia: A Systematic Review (The Review of Diabetic Studies, 2024)
Background: Saudi Arabia’s Vision 2030 encourages privatization and digital transformation to enhance healthcare quality, access and efficiency. While numerous digital health initiatives—such as telemedicine, electronic prescriptions and mobile health applications—have been introduced, their role in supporting the privatization of healthcare services remains unclear.Aim: This systematic review aimed to evaluate evidence on the role of digital health technologies in supporting the privatization of healthcare services in Saudi Arabia between 2020 and 2024.Method: Following PRISMA 2020 guidelines, a comprehensive search of PubMed/MEDLINE, Scopus, Web of Science, CINAHL, Embase and Google Scholar was conducted. Ten studies meeting predefined criteria were included. Data were extracted and synthesized narratively to identify themes related to access, efficiency, user perceptions, digital readiness, barriers, and policy contexts.Results: The studies demonstrated that digital health initiatives improved access to care, reduced unnecessary visits and generated cost savings, particularly through telemedicine and e‑prescription programs. Patients and clinicians generally held positive attitudes toward digital services, although adoption was uneven. Private hospitals exhibited higher digital maturity than public facilities, while low digital literacy, unreliable internet and cultural resistance emerged as major barriers. Government policies, including the Private Sector Participation Law and public–private partnerships, were pivotal in integrating digital health into privatization efforts.Conclusion: Digital health has considerable potential to advance healthcare privatization in Saudi Arabia by enhancing efficiency and patient experience. However, sustainable implementation will require targeted investments in infrastructure, workforce training and regulatory frameworks to address disparities and ensure equitable access.